Poland's Transformation : Facts and Myths about the Period 1990-2020 and the Country's Chances of Attaining the Economic Level of the USA and Germany after 2020 - Gomulka, Stanislaw (DEMO, 2020)
This paper studies path-breaking economic developments in Poland following the start of the systemic transformation in 1989. Three groups of countries are used for comparative analysis : those economically most advanced, those less developed but striving to catch up during the last 30-40 years, and as a subgroup of the latter, the transition economies. The paper has three objectives. The first is to show that many opinions regarding major aspects of the Polish transformation are at variance with the plain statistical facts. The second is to evaluate the pace and the extent of the progress so far in the effort to narrow the income and wealth gaps between Poland and most developed countries, particularly pre-2004 members of the European Union. The third consists of a discussion of factors which are likely to impede the pace of Poland ' s economic development in the years to come.(original abstract)